Development Planning in South Africa : Provincial Policy and State Power in the Eastern Cape. - Reynolds, John (Politics and development in contemporary Africa., 2018)
The first empirical study of the inner workings of South Africa's dysfunctional policy development process, exposing the challenges of large-scale policy overhaul and the frictions at the heart of the South African state.